Perancangan Sistem Informasi Inventori Gudang Pada PT.Del Citra Mandiri - Siagian, Yorris; Khairina, Nurul (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2025)
The development of information technology has encouraged PT. DEL Citra Mandiri, a radio broadcasting company, to adapt to the management of warehouse inventory that is still done manually using Microsoft Excel, is at risk of errors and data loss. This research aims to design a web-based inventory information system to improve the accuracy and efficiency of inbound and outbound goods management. This research uses a system development method based on a structured approach that includes analysis, design, implementation, and testing. System design is carried out with tools such as Flowchart, DFD, Use Case Diagram, and ERD. The technologies used include XAMPP as a local server, MySQL for databases, and Figma for user interface design. The results of the study show that the designed inventory information system is able to overcome the obstacles of manual recording, improve data accuracy, and facilitate real-time monitoring of stock of goods. With the implementation of this system, PT. DEL Citra Mandiri is expected to improve operational efficiency and support more accurate decision-making in warehouse management.